Impact of Thrombocytopenia on In-Hospital Outcome in Patients Undergoing Percutaneous Coronary Intervention - Zhongxiu Chen; Zheng Liu; Nan Li; Ran Liu; Miye Wang; Duolao Wang; Chen Li; Kai Li; Fangbo Luo; Yong He (Cardiovascular Therapeutics)
Background. Thrombocytopenia was intuitively considered to be associated with higher risk of bleeding and multiple comorbidities after percutaneous coronary intervention (PCI). However, controversial results exist, and the real-world clinical impact of thrombocytopenia in patients undergoing PCI is largely unknown. The aim of this study was to evaluate the influence of baseline thrombocytopenia on the prognosis of patients undergoing PCI. Methods. Using the West China Hospital Inpatient Sample database, patients who underwent PCI were identified from August 2012 to January 2019. Baseline thrombocytopenia was defined as a preprocedural platelet count of 100×109/L or less obtained from a routine blood sample taken within 48 hours before coronary PCI. The clinical effect of the advanced thrombocytopenia group (≤85×109/L), according to the median value of platelet count in the thrombocytopenia cohort, was further assessed. The primary outcome was a composite of in-hospital death, bleeding events, and post-PCI transfusion. Results. Of 9531 patients enrolled in our study, 936 had baseline thrombocytopenia and 8595 patients did not have. There were no significant differences in the primary outcome between the two groups. However, advanced thrombocytopenia was independently associated with higher risk of primary outcome (OR 1.67, 95% CI 1.06 to 2.65, p=0.029). Acute coronary syndrome (ACS) patients with thrombocytopenia were associated with higher odds of major bleeding (BARC≥2) (OR 2.56, 95% CI 1.24 to 5.44, p=0.011). Compared with the nonthrombocytopenia group, the thrombocytopenia group with ticagrelor use had higher odds of major bleeding (OR 9.7, 95% CI 1.57 to 60.4 versus OR 0.22, 95% CI 0.03 to 1.69, interaction p=0.025). Conclusions. It seems feasible for patients with thrombocytopenia to receive PCI, but close attention should be paid to advanced thrombocytopenia, the risk of postprocedure bleeding in ACS patients, and the use of more potent P2Y12 inhibitor.